Narasi dan Wacana Komunikasi Politik Prabowo–Gibran dalam Kontestasi Pemilu 2024 - Siti Rohmah; Meriwijaya . (Jurnal DinamikA, 2025)
Social media has transformed into a primary arena for shaping public opinion and political image in the digital era. This study aims to examine the narrative construction and discourse of the Prabowo-Gibran political communication pair in the 2024 election contest. This study is based on political communication theory, which highlights how symbols, language, and representation shape public perception. The method used is a qualitative content analysis approach, through tracing messages and symbols that appear on Prabowo and Gibran's personal social media channels, such as TikTok, Instagram, and YouTube channels, accompanied by reading netizen responses and online media coverage. The results of the study show that the Prabowo-Gibran pair implemented a digital populism-based communication strategy by combining humor, emotional closeness, and digital technology. The "gemoy" image and popular symbols such as the "Samsul Jacket" and the Uzumaki Naruto character are not just gimmicks, but rather a form of cultural rebranding that adapts the campaign style to the digital culture of young people. The use of Artificial Intelligence (AI) technology in campaign materials also strengthens the narrative of modernity and efficiency. These findings emphasize the shift in political communication towards an entertainment format (politainment) that not only expands the reach of political messages but also strengthens the symbolic relationship between candidates and voters. Theoretically, this study enriches the study of digital political communication through an analysis of the role of narrative and discourse in the formation of political images in contemporary virtual spaces.